Aluminum Phosphide Poisoning Mortality Rate in Iran; a Systematic Review and Meta-Analysis - Bagherian, Farhad; Kalani, Navid; Rahmanian, Fatemeh; Abiri, Samaneh; Hatami, Naser; Foroughian, Mahdi; John Mehramiz, Neema; Shahi, Behzad (Archives of Academic Emergency Medicine, 2021)
Introduction: According to statistics provided by the forensic medicine facility of Iran, there are a high number of Aluminum phosphide (ALP) poisoning-related deaths in the country; while the mortality rate varies in different studies. This study aimed to determine a pooled estimate of ALP poisoning mortality rate in Iran. Methods: The present study was a systematic review and meta-analysis of the mortality rate of ALP poisoning in Iran. Through the quarry of Persian and English databases, using “aluminum phosphide”, “phosphine”, “rice pills”, “poisoning”, and “Iran” as keywords, and no time restrictions, studies reporting mortality rate in ALP poisoning cases were collected. The random-effects model was used to pool the proportions of mortality and age of survivors versus non-survivors. Results: 21 studies with 3432 cases of ALP poisoning were included in this meta-analysis. The pooled mortality rate of ALP poisoning in Iran was 39.6%, (95% CI: 31.5%-47.9%; I2 = 95%). Since there was significant publication bias, the trim-and-fill correction was conducted and the corrected pooled mortality rate was estimated to be 27.3% (95% CI: 18.9%- 36.5%), which is the rate that should be considered for clinical guidance. Morality rate in male and female patients was 62.3% (95% CI: 53.5%-70.8%) and 37.7% (95% CI: 29.2%-46.5%), respectively (p < 0.01). Survivors had significantly lower mean age than non-survivors (SMD: -0.26 (95% CI: -0.37 to -0.15); p < 0.01; I2=0%). Conclusion: According to this report, the Mortality rate of ALP poisoning in Iranian population is about 27%, with men having a higher fatality rate than women. Poisoning at a younger age is associated with better results.